Long-term survival in patients with advanced non–small-cell lung cancer treated with atezolizumab versus docetaxel: Results from the randomised phase III OAK study. (January 2019) - von Pawel, J.; Bordoni, R.; Satouchi, M.; Fehrenbacher, L.; Cobo, M.; Han, J.Y.; Hida, T.; Moro-Sibilot, D.; Conkling, P.; Gandara, D.R.; Rittmeyer, A.; Gandhi, M.; et al.
Abstract: Background: Atezolizumab (anti–programmed death-ligand 1 [PD-L1]) received approval from the US Food and Drug Administration and European Medicines Agency for previously treated advanced non–small-cell lung cancer based on OAK—a randomised, phase III trial that showed significantly improved survival with atezolizumab versus docetaxel regardless of PD-L1 expression. With longer follow-up, we summarised the characteristics of long-term survivors (LTSs). Methods: In OAK (NCT02008227), patients were randomised 1:1 to receive atezolizumab or docetaxel until loss of clinical benefit or disease progression, respectively. Overall survival was evaluated after a 26-month minimum follow-up, including in patient subgroups defined by best overall response (BOR). LTSs were defined as patients who lived ≥24 months since randomisation. Non-LTSs died within 24 months, and patients censored before 24 months were excluded from the analysis. The baseline characteristics, including biomarkers, BOR, subsequent non-protocol therapy (NPT) and safety, are reported. Results: Survival benefit with atezolizumab was observed across all patient subgroups defined by BOR. More atezolizumab-treated patients were LTSs versus those treated with docetaxel (28% versus 18%). Most atezolizumab responders were LTSs (77%) versus only 48% of docetaxel responders. However, 21% of atezolizumab-arm LTSs had progressive disease (PD) as BOR, and more atezolizumab-arm LTSs than non-LTSs continued treatment post-PD. Fifty-two percent of docetaxel-arm LTSs received immunotherapy as subsequent NPT. Despite extended treatment duration in atezolizumab-arm LTSs (median, 18 months), atezolizumab was well tolerated. Conclusions: After >2 years of follow-up, atezolizumab continued to provide durable survival benefit versus docetaxel, with tolerable safety. Atezolizumab-arm LTSs were enriched for patients with high PD-L1 expression and included PD-L1–negative patients. Long-term survival was not limited to responders. Highlights: Atezolizumab provided durable survival benefit across all best-response subgroups. Atezolizumab long-term survivors (LTSs) were enriched for high programmed death-ligand 1 (PD-L1) expression. Atezolizumab LTSs also included patients with PD-L1–negative tumours. Atezolizumab LTSs included patients with progressive disease as best response. Extended atezolizumab exposure showed tolerable safety in LTS.